2007
DOI: 10.1111/j.1748-5827.2007.00470.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the prevalence of enteric viruses in healthy dogs and those with acute haemorrhagic diarrhoea by electron microscopy

Abstract: Results suggest that shedding of parvovirus and paramyxovirus is strongly associated with acute haemorrhagic diarrhoea. However, coronavirus seems to be even more prevalent among healthy dogs, raising the need for further studies to investigate the strain-associated pathogenicity of this virus.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
38
3
5

Year Published

2008
2008
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(54 citation statements)
references
References 20 publications
(32 reference statements)
8
38
3
5
Order By: Relevance
“…Infectious causes evaluated in this study were limited to parasitic or algae infections, and no viral or obligate enteropathogenic bacteria were identified as a primary cause of chronic diarrhea. Potentially pathogenic organisms can be frequently found in the feces of clinically healthy dogs and dogs with chronic enteropathy making it difficult to determine whether a specific organism identified acts as an etiologic factor, is a result of a changing microbiota due to the chronic enteropathy, or is in fact unrelated to the disease process . With respect to the multifactorial etiology of chronic enteropathies, the resolution of clinical signs after elimination of the identified organism is essential to determine disease causation .…”
Section: Discussionmentioning
confidence: 99%
“…Infectious causes evaluated in this study were limited to parasitic or algae infections, and no viral or obligate enteropathogenic bacteria were identified as a primary cause of chronic diarrhea. Potentially pathogenic organisms can be frequently found in the feces of clinically healthy dogs and dogs with chronic enteropathy making it difficult to determine whether a specific organism identified acts as an etiologic factor, is a result of a changing microbiota due to the chronic enteropathy, or is in fact unrelated to the disease process . With respect to the multifactorial etiology of chronic enteropathies, the resolution of clinical signs after elimination of the identified organism is essential to determine disease causation .…”
Section: Discussionmentioning
confidence: 99%
“…Canine Coronavirus (CCoV) is an important enteropathogen of dogs, as it has caused many outbreaks (Decaro and Buonavoglia, 2008). CCoV is widespread in canine population, mainly in kennels and shelters, which are overcrowded, according to serological and virological investigations (Naylor et al, 2001;Schulz et al, 2008). Infection with Canine Coronavirus is characterised by high morbidity and low mortality and it is transmitted via the fecal-oral route (Tennant et al, 1991).…”
Section: Coronavirusesmentioning
confidence: 99%
“…Since then, several CCoV outbreaks have been reported worldwide, showing that CCoV is an important enteropathogen of the dog. Serological and virological investigations have demonstrated that CCoV is widespread in dog population, mainly in kennels and animal shelters (Carmichael, 1978;Rimmelzwaan et al, 1991;Tennant et al, 1993;Möstl et al, 1994;Bandai et al, 1999;Naylor et al, 2001b;Yeşilbag et al, 2004;Schulz et al, 2008). CCoV infection is characterised by high morbidity and low mortality, as well as by a typical faecal-oral route of transmission (Tennant et al, 1991).…”
Section: History and Pathobiologymentioning
confidence: 99%